Antithrombotic strategies after transcatheter aortic valve implantation: Insights from a network meta‐analysis. Issue 2 (14th October 2019) - Kuno, Toshiki; Takagi, Hisato; Sugiyama, Takehiro; Ando, Tomo; Miyashita, Satoshi; Valentin, Nelson; Shimada, Yuichi J.; Kodaira, Masaki; Numasawa, Yohei; Kanei, Yumiko; Hayashida, Kentaro; Bangalore, Sripal
Abstract : Objectives: We aimed to investigate the efficacy and safety of different antithrombotic strategies in patients undergoing transcatheter aortic valve implantation (TAVI) using network meta‐analyses. Background: Meta‐analyses comparing single antiplatelet therapy (SAPT) vs. dual antiplatelet therapy (DAPT), ± oral anticoagulant (OAC) was conducted to determine the appropriate post TAVI antithrombotic regimen. However, there was limited direct comparisons across the different therapeutic strategies. Methods: MEDLINE and EMBASE were searched through December 2018 to investigate the efficacy and safety of different antithrombotic strategies (SAPT, DAPT, OAC, OAC + SAPT, and OAC + DAPT) in patients undergoing TAVI. The main outcome were all‐cause mortality, major or life‐threatening bleeding events, and stroke. Results: Our search identified 3 randomized controlled trials and 10 nonrandomized studies, a total of 20, 548 patients who underwent TAVI. All OACs were vitamin K antagonists. There was no significant difference on mortality except that OAC + DAPT had significantly higher rates of mortality compared with others ( p < .05, I 2 = 0%). SAPT had significantly lower rates of bleeding compared with DAPT, OAC+SAPT, and OAC+DAPT (hazard ratio [HR]: 0.59 [0.46‐0.77], p < .001, HR: 0.58 [0.34‐0.99], p = .045, HR: 0.41 [0.18‐0.93], p = .033, respectively, I 2 = 0%). There was no significant difference on stroke among all antithrombotic strategies. Conclusion: Patients who underwent TAVI had similar all‐cause mortality rates among different antithrombotic strategies except OAC+DAPT. Patients on SAPT had significantly lower bleeding risk than those on DAPT, OAC + SAPT, and OAC + DAPT. Our results suggest SAPT is the preferred regimen when there is no indication for DAPT or OAC. When DAPT or OAC is indicated, DAPT + OAC should be avoided.